Estimation of the Atmospheric Ice Content Mass, Spatial Distribution, and Long‐Term Changes Based on the ERA5 Reanalysis. Issue 15 (3rd August 2020) - Dou, T.; Xiao, C.; Huang, Y.; Yue, H.; Han, W.
Abstract: The aerial cryosphere refers to all ice bodies in the atmosphere and has important impacts on the development of weather systems, climate change, and aviation safety. The total mass of the aerial cryosphere is evaluated for the first time based on the fifth generation European Centre for Medium‐Range Weather Forecasts reanalysis (ERA5) reanalysis data set, and the spatiotemporal variability and long‐term change of the aerial cryosphere are investigated. The results show that the total mass of atmospheric ice is approximately 33.1 Gt [29.7–37.0 Gt], covering 74.3% of the Earth's surface area with obvious latitudinal zonality and seasonal variability. The aerial cryosphere mass has been increasing over the past few decades due to the overall increase in the atmospheric water vapor content caused by rising global temperatures. Moreover, the contribution of warming to the ablation of the aerial cryosphere is negligible since there is no significant trend in the height of the atmospheric freezing point layer. Plain Language Summary: Ice in the atmosphere appears as in the form of cloud ice crystals, snowflakes, and graupel, among others. Unlike the ice that forms on the land and sea, this ice is collectively known as the aerial cryosphere. For many years, we did not understand how much is this portion of ice or how it is changing, either spatially or temporally. Here, for the first time, we estimate the total mass of the aerial cryosphere using the fifth generation European Centre for Medium‐Range Weather Forecasts (ECMWF) atmospheric reanalysis (ERA5) global climate data set. The results show that the total global mass of atmospheric ice bodies is approximately 33.1 Gt [29.7–37.0 Gt], covering 74.3% of the Earth's surface area. Beyond our initial expectation, the aerial cryosphere mass has been increasing in recent decades due to the overall increase in the atmospheric water vapor content caused by rising global temperatures. However, the rise in the base height of the atmospheric freezing point layer is not significant; therefore, the contribution of warming to the ablation of the aerial cryosphere is negligible. The increase in the aerial cryosphere mass does not reflect the amount of ground snowfall and snow cover, probably due to the warming of the lower troposphere during the same period. Key Points: The total mass of the ice in the global atmosphere has been estimated for the first time The aerial cryosphere has a mass of about 33.1 Gt and covers 74.3% of global surface area with obvious latitudinal zonality The aerial cryosphere has increased over the past decades due to the increased water vapor in the atmosphere caused by global warming